2011
DOI: 10.1063/1.3602994
|View full text |Cite
|
Sign up to set email alerts
|

Topology effects of interface and gate voltage on electrical transport through the CNT/C60/CNT junction using the Green’s function method

Abstract: PAMELA: An open-source software package for calculating nonlocal exact exchange effects on electron gases in core-shell nanowires AIP Advances 2, 032173 (2012) Tunable electronic transport characteristics through an AA-stacked bilayer graphene with magnetoelectric barriers J. Appl. Phys. 112, 053714 (2012) Pinned interface dipole-induced tunneling electroresistance in ferroelectric tunnel junctions: A theoretical investigation J. Appl. Phys. 112, 054104 (2012) Current-voltage characteristics and ON/OFF rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…70 Moreover, the effect of a gate voltage is observed as a shift in the peaks of transmission. 71 Therefore, in Fig. 6, we simply calculate the variations of thermoelectric properties as a function of the shift of the Fermi level in the equilibrium transmission spectra.…”
Section: Effect Of Fermi Level Shiftmentioning
confidence: 99%
“…70 Moreover, the effect of a gate voltage is observed as a shift in the peaks of transmission. 71 Therefore, in Fig. 6, we simply calculate the variations of thermoelectric properties as a function of the shift of the Fermi level in the equilibrium transmission spectra.…”
Section: Effect Of Fermi Level Shiftmentioning
confidence: 99%
“…They found that the I-V characteristics could be changed from metallic behavior to semiconducting by a gate potential, thereby forming a field-effect molecular current switch. Saffarzaden 21 and Shokri et al 22 respectively investigated electron transport across a carbon molecular junction consisting of a C 60 molecule attached to two one-dimensional electrodes and semi-infinite metallic open-end CNT leads. They found that a gate voltage could shift the molecular levels, where the electron conduction could be controlled by adjusting the related parameters.…”
Section: Introductionmentioning
confidence: 99%
“…3 Particularly, several authors have studied the molecular junctions of the C 60 fullerene under different types of connections, such as a substrate and a STM tip, 4,5 one-dimensional leads, 6 carbon nanotubes (CNTs), 7 gold clusters, 8 or break junctions. 9 Furthermore, the stability and strong hybridization of C 60 with metallic surfaces make it also a feasible anchoring group with high conductance.…”
Section: Introductionmentioning
confidence: 99%